Estimation of Air Pollutant Transportation Equation in Surabaya using Kalman Filter Method - Didik Khusnul Arif; Helisyah Nur Fadhilah; Prima Aditya ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2020)
Surabaya is one of big cities in Indonesia. Since the number of industries in Surabaya is increasing, the level of air pollution in Surabaya is also increasing. To deal with this matter, procurement of measuring instruments has been carried out in several locations in Surabaya based on the level of emissions issued by motorized vehicles, but increasing the number of measuring instruments affects the cost significantly. Therefore, the estimation of air pollution will make it easier to determine the level of air pollution in Indonesia. Kalman filter a method to estimate the state variable by using a system model accompanied by a measurement model as the initial value that comprises the prediction stage and the correction stage. The results of this correction stage will be the estimation results. Then it will be compared with the data at some locations. The results obtained are quite accurate at the point of observation with a relatively small error.